PENERAPAN PROGRAM TIE-DYE TOTE BAG PADA ORANG DENGAN SKIZOFRENIA (ODS) - Naomi Soetikno; Naftali Keisya; Yolly Amelia; Binsar Adi Saputro (PROSIDING SERINA, 2021)
People with Schizophrenia will experience both positive and negative symptoms. In positive symptom, they will experience additional characteristics that should not exist in normal situations, such with the appearance of hallucinations, delusions, as well as the presence of disorganized behavior and speech. Whereas, in negative symptoms, they will experience a decrease or loss of existing characteristic, such as loss or decrease in emotion, intensity of speech, and interest in doing something. Lack of interest and motivation to perform an activity with a purpose in people with Schizophrenia was found to be associated with an increase of their presence of positive symptoms. The use of art therapy is often used as an effort to improve the recovery of people with Schizophrenia and has been proven through various studies. The implementation of tie-dye tote bag program as a form of activity in psychosocial care are provided to participants with Schizophrenia who are partners in humanitarian projects at Pelita Jiwa Foundation, Tangerang. The results obtained indicate that people with Schizophrenia benefit in feel happier, less boredom, and increased interest in participating in the program. This program can also be used as an art activity in psychosocial care for people with Schizophrenia. Additional benefits are also obtained from providing psychoeducation of people with Schizophrenia to caregivers at the foundation.